1995
DOI: 10.1364/josab.12.002117
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band β-BaB_2O_4 optical parametric oscillator in a grazing-incidence configuration

Abstract: The key operating parameters of a grazing-incidence optical parametric oscillator (GIOPO) based on b-BaB 2 O 4 pumped by the third harmonic of a Nd:YAG laser are studied. The bandwidth of the GIOPO is investigated as a function of both the pump-laser bandwidth and the incident angle on the diffraction grating. The efficiency of the device is investigated by measurement of both the depletion of the pump laser and the output of the GIOPO. The results indicate a strong dependence of the bandwidth of the GIOPO on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Now, because of the invariance under the tilde conjugation for |φ given by Eqs. (23), (24) and (25), we obtain µ * = ν, that is to say,…”
Section: Definitions Of Thermal Coherent Statesmentioning
confidence: 75%
See 1 more Smart Citation
“…Now, because of the invariance under the tilde conjugation for |φ given by Eqs. (23), (24) and (25), we obtain µ * = ν, that is to say,…”
Section: Definitions Of Thermal Coherent Statesmentioning
confidence: 75%
“…The OPO-based laser system is constructed out of the OPO with ring resonators as shown in Figs. 5 and 6 [22,23,24,25]. In Fig.…”
Section: Definitions Of Thermal Coherent Statesmentioning
confidence: 99%
“…4 This configuration has also been used to minimize the bandwidth of an OPO based on b-BaB 2 O 4 (BBO), as we reported recently. 5 However, the external eff iciency of such a cavity was low, and we found stable SLM operation diff icult to achieve.…”
mentioning
confidence: 78%
“…Gloster et al [19] reported walk-off compensated BBO OPO pumped by third harmonic of Nd:YAG laser radiation having 30 GHz linewidth at grazing angle of incidence configuration. They observed decrease in linewidth of the generated radiation with increasing grating angle.…”
Section: Grazing Angle Of Incidence Configurationmentioning
confidence: 99%